Risky Sexual Behavior among Men Who Have Sex with Men (MSM) in Indonesia: A Literature Review - Putri, Fridya Syavina; Herbawani, Chahya Kharin (Fakultas Kedokteran, 2024)
Background: Men Who Have Sex with Men (MSM) is a phenomenon where men have sex with other men. MSM behavior puts them at risk for STIs or HIV/AIDS. Globally, gays and MSM account for about 17% of new cases of HIV infection, including 30% in Asia and the Pacific. Meanwhile, according to the Ministry of Health, the MSM population group will be the highest HIV contributor group in 2021 (quarter 1). Objectives: This literature review aims to determine the description of risky sexual behavior among MSM in Indonesia. Method: This study uses a literature review method sourced from Google Scholar, ScienceDirect, and Garuda in the range of 2013-2023. Result: From 8 journals that have passed the inclusion and exclusion process, it was found that MSM often have risky sexual relationships such as having anal sex, not using condoms, not doing VCT, and sexual positions as receptive (bottom). The determinants of MSM behavior were influenced by environmental, psychological, economic, behavioral, and parental factors. Conclusion: The sexual behavior of MSM is more risky for virus transmission including HIV. Meanwhile, the most dominant determinant of MSM behavior in this literature is parental factors.